The Quality of Human Resources, Job Performance and Employee Loyalty - Darmawan, Didit; Mardikaningsih, Rahayu; Anastasya Sinambela, Ella; Arifin, Samsul; Rachman Putra, Arif; Hariani, Mila; Irfan, Mochamad; Rahman Al Hakim, Yusuf (International Journal of Psychosocial Rehabilitation, 2020)
Job performance and employee loyalty are concepts of human resources that have been popular because they will influence the success of the company to achieve its goals. The company's objectives to be achieved should also be supported by quality human resources. The challenges facing the company are how to place employees in the right position, maximizing employees in accordance with the quality and needs of the company. This study aims to analyze and determine the effect of the quality of human resources on job performance and job loyalty. A total of 113 employees have been involved in this study. This study uses a path analysis tool through the SPSS program with a simple tiered regression analysis. The results showed that (1) the quality of HR has a real influence on job performance; (2) the quality of human resources has a real influence on employee loyalty; and (3) job performance has a real influence on employee loyalty.